Development of the instrument for implementing the Islamic way of life guidelines among Muhammadiyah Community - Subando, Joko; Muslimin, Edy; Samsuri, Muh; Sarilan, Sarilan (Measurement In Educational Research, 2024)
This study aims to develop a measurement instrument for the implementation of Islamic lifestyle guidelines among Muhammadiyah community members. The research procedure adapts Borg and Gall's development research model. The steps in instrument development include preliminary research, planning, initial product development, limited testing, and expanded testing. Five experts were involved in the development of the initial product, with expertise covering measurement, religious thought, and Muhammadiyah practice. The expert assessment data were analyzed using the Aiken formula. Twenty-five Muhammadiyah leaders in Karanyanyar participated in the limited testing phase, and the data from this phase were analyzed using exploratory factor analysis with SPSS. The expanded testing involved 253 leaders and members of Muhammadiyah in the districts of Karanganyar, Sragen, and Boyolali, selected using the cluster random sampling technique. The data from the expanded testing were analyzed using confirmatory factor analysis and structural equation modeling (SEM) with LISREL software. The research resulted in a package of 27 valid and reliable measurement items for the implementation of Islamic lifestyle guidelines among Muhammadiyah members, suitable for further measurement.